3*(2x-1)+7=5*(x-1)+7
3,1*(1-3t)+t=0,4*(t-14)
0,8*(0,5-2u)=2u+0,4
0,2*(x-3)-1=0,5*(x+3)-0,4
-5*(z-7)=30-(2z+1)
-2*(x+5)+3=2-3*(x+1)
3*(2x-1)+6x=10x-7
4n-2*(n+7)=2n-2*(n-1)

1

Ответы и объяснения

2014-04-01T15:19:34+04:00

1)3*(2x-1)+7=5*(x-1)+7
6х-3+7=5х-5+7
6х+4=5х+2
6х-5х=2-4
х=-2
2)3,1*(1-3t)+t=0,4*(t-14)
3,1-9,3t+t=0,4t-5,6
3,1-8,3t=0,4t-5,6
3,1+5,6=0,4t+8,3t
8,7=8,7t
t=1
3) 0,8*(0,5-2u)=2u+0,4
0,4-1,6u=2u+0,4
0,4-0,4=1,6u+2u
0=3,6u
u=0
4)0,2*(x-3)-1=0,5*(x+3)-0,4
0,2х-0,6-1=0,5х+1,5-0,4

 0,2х-1,6=0,5х+1,1
0,2х-0,5х=1,1+1,6
-0,3х=2,7
х=-9
5)-5*(z-7)=30-(2z+1)
-5
z+35=30-2z-1

 -5z+35=29-2z
-5z+2z=29-35
-3z=-6
z=2
6)-2*(x+5)+3=2-3*(x+1)
-2х-10+3=2-3х-3

-2х-7=-1-3х
-2х+3х=-1+7
Х=6
7) 3*(2x-1)+6x=10x-7
6х-3+6х=10х-7

12х-3=10х-7
12х-10х=-7+3
2х=-4 х=-2
 8) 4n-2*(n+7)=2n-2*(n-1)
 4n-2n-14=2n-2n+2
2n-14=2
2n=2+14
 2n=16
 n=8